2003
DOI: 10.1614/wt-03-004r1
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Extension Rate May Help Determine When Low Wild Oat Herbicide Rates Will Be Effective1

Abstract: Determination of the active growth state of weeds may lead to more reliable predictions of herbicide efficacy. Experiments were conducted at Lacombe and Lethbridge, Alberta, Canada, from 1996 to 1998 to determine if wild oat leaf extension (growth) rate could be used to predict the efficacy of imazamethabenz and ICIA 0604. As expected, wild oat control increased and wild oat biomass decreased with increasing imazamethabenz and ICIA 0604 rates. Mean wild oat growth rates ranged from 6 to 44 mm over a 24-h time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…A recent study measured the leaf extension rate of wild oat as an indicator of “active growth” and found that the efficacy of reduced doses of tralkoxydim and imazamethabenz was correlated with greater wild oat leaf growth (Fig. 1; Harker & Blackshaw 2003). Perhaps farmers could utilize this simple method of assessing weed growth in their decision‐making process when considering reduced herbicide doses.…”
Section: Enhancing the Successful Use Of Reduced Herbicide Dosesmentioning
confidence: 99%
“…A recent study measured the leaf extension rate of wild oat as an indicator of “active growth” and found that the efficacy of reduced doses of tralkoxydim and imazamethabenz was correlated with greater wild oat leaf growth (Fig. 1; Harker & Blackshaw 2003). Perhaps farmers could utilize this simple method of assessing weed growth in their decision‐making process when considering reduced herbicide doses.…”
Section: Enhancing the Successful Use Of Reduced Herbicide Dosesmentioning
confidence: 99%
“…Several authors have suggested that environmental conditions before, during and after herbicide application are an important basis for determining the reduced dose rate (Caseley, 1987, 1989; Kudsk, 1989; Kudsk & Kristensen, 1992; Lundkvist, 1997a; Collings et al. , 2003; Harker & Blackshaw, 2003; Madafiglio et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many herbicide labels recommend application when weeds are actively growing and that efficacy can be reduced under poor growing conditions or when plants are stressed. As pointed out by Harker and Blackshaw (2003), none of the instructions indicate what good growing conditions are or how actively growing weeds can be identified. Those authors found that Avena spp.…”
Section: Discussionmentioning
confidence: 99%
“…, 1974) at the time of spraying. Leaf extension rates were also recorded in 2003 for a 24 h period around the time of spraying, as described by Harker and Blackshaw (2003). Analyses of the data collected in 2003 indicated that Avena spp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation